2018
DOI: 10.3389/fmicb.2018.00672
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Growth of Rhodococcus aetherivorans BCP1 Using Selected Naphthenic Acids as the Sole Carbon and Energy Sources

Abstract: Naphthenic acids (NAs) are an important group of toxic organic compounds naturally occurring in hydrocarbon deposits. This work shows that Rhodococcus aetherivorans BCP1 cells not only utilize a mixture of eight different NAs (8XNAs) for growth but they are also capable of marked degradation of two model NAs, cyclohexanecarboxylic acid (CHCA) and cyclopentanecarboxylic acid (CPCA) when supplied at concentrations from 50 to 500 mgL-1. The growth curves of BCP1 on 8XNAs, CHCA, and CPCA showed an initial lag phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 71 publications
1
42
0
Order By: Relevance
“…These observations are in line with other studies where the membrane fluidity and permeability of Pseudomonas cells were compromised by excesses of ethanol [48]. Reasonably, the accumulation of lipophilic compounds between the acyl chains of the phospholipid bilayers led to the alteration of the membrane properties through a process known as narcosis [27,49], which can eventually determine swelling of the phospholipid bilayer, causing the transition towards round-shape morphology [50]. Further, both strains were capable of synthesizing electron transparent intracellular accumulations (Figure 2A-C indicated by black dashed arrows) likely containing hydrophobic storage compounds (e.g., polyhydroxyalkanoates), which were elsewhere reported to act as carbon and energy-reserve material by most microorganisms, since these storage compounds are produced by bacteria when they experience unbalanced nutritional conditions and/or environmental stresses [51,52].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These observations are in line with other studies where the membrane fluidity and permeability of Pseudomonas cells were compromised by excesses of ethanol [48]. Reasonably, the accumulation of lipophilic compounds between the acyl chains of the phospholipid bilayers led to the alteration of the membrane properties through a process known as narcosis [27,49], which can eventually determine swelling of the phospholipid bilayer, causing the transition towards round-shape morphology [50]. Further, both strains were capable of synthesizing electron transparent intracellular accumulations (Figure 2A-C indicated by black dashed arrows) likely containing hydrophobic storage compounds (e.g., polyhydroxyalkanoates), which were elsewhere reported to act as carbon and energy-reserve material by most microorganisms, since these storage compounds are produced by bacteria when they experience unbalanced nutritional conditions and/or environmental stresses [51,52].…”
Section: Resultssupporting
confidence: 90%
“…Bacterial cells grew up to the late exponential growth phase (72-h) under ethanol:octane (PS27) or octane (PDMF10) conditioning, and in the presence/absence of 50 µM PFHxS were collected, thin sectioned and imaged through Philips CM100 TEM operating at 80 kV, as described by Presentato and co-workers (2018) [27]. Briefly, the bacterial cells were fixed for 2-h at room temperature (RT) with a primary fixative solution composed of: glutaraldehyde (2.5% v/v), HEPES (50 mM) and magnesium chloride (MgCl 2 ; 1 mM) at pH7, being successively rinsed 3 times with sodium cacodylate buffer (0.1 M) pH 7.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Strain R. erythropolis DCL14 produced PUFA when the cells were adapted to conditions previously considered as extreme for non-adapted cells: when the cells grew at 4 °C, at pH 4–10 (but not at pH 3 or 11) and in the presence of challenging amounts of NaCl and CuSO 4 in the growth medium [ 60 ]. It was recently reported that R. aetherivorans BCP1 produces PUFA when using naphthenic acids as sole carbon and energy sources [ 101 ].…”
Section: Fatty Acids As Modulators Of Membrane Propertiesmentioning
confidence: 99%
“…Actually, the infections due to Gram-negative bacteria are more difficult to eradicate [ 3 , 32 ]. Thus, we assume that the perfluoroalkyl chains could allow the penetration of both compounds into Gram-negative bacteria and lead to the accumulation of these complexes into the phospholipid bilayers of the cytoplasmic membrane with the consequent alteration of the membrane properties through a process known as narcosis [ 31 , 33 , 34 ] and with the resultant cell death. This assumption is supported by the report of Wójcik et al, 2018 [ 35 ] that demonstrated the incorporation of perfluorinated compounds into model membranes resembling those typical to Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%